Synthesis and Crystal Structure of New Trinuclear Nickel(II) Complex [(NiL)2(OAc)2Ni].n-BuOH·CHCl32·n-BuOH - Sun, Yin-Xia; Lu, Rui-E; Zhang, Yu-Jie; Meng, Wei-Sheng; Li, Xin-Ran (Asian Journal of Chemistry, 2013)
A new trinuclear nickel(II) complex with a Salen-type bisoxime chelating ligand (H2L), [(NiL)2(OAc)2Ni]·n-BuOH·CHCl32·n-BuOH, has been synthesized and characterized. The X-ray crystal structure of the Ni(II) complex reveals that the unit cell contains two crystallographically independent but chemical identical trinuclear Ni(II) complexes, molecules A and B. Interestingly, the complex possessing different conformational metal centers: penta- and hexa-coordinated geometry. The coordination geometry around the terminal Ni2 and Ni2#1 atom in molecule A (Ni4 and Ni4# in molecule B) approaches a distorted square pyramid. The coordination sphere of the central Ni1 atom in molecule A (Ni3 in molecule B) constitutes a slightly distorted octahedral geometry.